De novo sequencing, characterization, and comparison of inflorescence transcriptomes of Cornus canadensis and C. florida (Cornaceae). - Jian Zhang (PLoS ONE, 2013)
BACKGROUND: Transcriptome sequencing analysis is a powerful tool in molecular genetics and evolutionary biology. Here we report the results of de novo 454 sequencing, characterization, and comparison of inflorescence transcriptomes of two closely related dogwood species, Cornus canadensis and C. florida (Cornaceae). Our goals were to build a preliminary source of genome sequence data, and to identify genes potentially expressed differentially between the inflorescence transcriptomes for these important horticultural species. RESULTS: The sequencing of cDNAs from inflorescence buds of C. canadensis (cc) and C. florida (cf), and normalized cDNAs from leaves of C. canadensis resulted in 251799 (ccBud), 96245 (ccLeaf) and 114648 (cfBud) raw reads, respectively. The de novo assembly of the high quality (HQ) reads resulted in 36088, 17802 and 21210 unigenes for ccBud, ccLeaf and cfBud. A reference transcriptome for C. canadensis was built by assembling HQ reads of ccBud and ccLeaf, containing 40884 unigenes. Reference mapping and comparative analyses found 10926 sequences were putatively specific to ccBud, and 6979 putatively specific to cfBud. Putative differentially expressed genes between ccBud and cfBud that are related to flower development and/or stress response were identified among 7718 shared sequences by ccBud and cfBud. Bi-directional BLAST found 87 (41.83% of 208) of Arabidopsis genes related to inflorescence development had putative orthologs in the dogwood transcriptomes. Comparisons of the shared sequences by ccBud and cfBud yielded 65931 high quality SNPs between two species. The twenty unigenes with the most SNPs are listed as potential genetic markers for evolutionary studies. CONCLUSIONS: The data provide an important, although preliminary, information platform for functional genomics and evolutionary developmental biology in Cornus. The study identified putative candidates potentially involved in the genetic regulation of inflorescence evolution and/or disease resistance in dogwoods for future analyses. Results of the study also provide markers useful for dogwood phylogenomic studies.